Conductivity of Strontium Soaps in water - Verma, Anjali (Asian Journal of Chemistry, 2010)
Conductivity data of strontium soaps (valerate, caproate and caprylate) solutions have been used to evaluate the true dissociation constant, limiting molar conductivity and thermodynamic parameters, viz., enthalpy, free energy and entropy changes of dissociation. The soaps behave as a weak electrolyte in water and Oebye-Huckel-Onsager equation is not applicable for these soap solutions.